Rumah terbuka Aidilfitri: visitors satisfaction and revisit intention towards Malaysian eid festivity / Nursyafiqah Ramli - Ramli, Nursyafiqah (2013)
Malaysia is recognized as one of the unique countries through its multiethnic populations which consist of the Malays, Chinese, Indians and other Indigenous groups. Each of the ethnic group has their own traditional culture and celebrates their festivals yearly. The major ethnics’ festivals celebrations such as Hari Raya Aidilfitri (Malays), Deepavali (Indians) and Chinese New Year (Chinese) have been recognized by the Malaysian government to be a national celebration and yearly events. These events are popularly known as “Rumah Terbuka”. Even though the celebration of “Rumah Terbuka” festivals have been started and celebrated few years ago, each manages to attract a huge crowd from different ethnicities and backgrounds. However, people are willing to spend time queuing which sometimes could stretch into long hours before they can be seated and enjoy the “Rumah Terbuka” festivals. Therefore, this study empirically examined the factors that influence visitors to attend the Rumah Terbuka Aidilfitri festival, level of visitors’ satisfaction and intention to revisit the festival. Using the Rumah Terbuka Aidilfitri festival in Perak as the contextual setting, the visitors were given questionnaires to be answered. Through series of analyses, some useful insights or predictors on the issue of interest were obtained. Majority of the respondents demonstrated positive responses on the attributes of the festival. Most agreed that the program was well organized, suited to all ages and unique. Varieties of foods were served to the visitors including traditional food from different cultures. Facilities and amenities provided were adequate and cater to the visitors’ needs while the venue chosen for the festival was interesting and appeal to the visitors. Various entertainment and shows were also performed during the festival to keep the visitors entertained. It was also found that they were satisfied with the festival and would return to this particular festival again as well as recommending the festival to others. Therefore, improvement needs to be done by the government authorities or the organizer in planning and managing such festival in order to increase visitor’s satisfaction and revisit intention. The findings for this study could contribute to the body of knowledge regarding those factors associated with visitors’ satisfaction and behavioral intentions towards festivals.